Mass spectrometry imaging in the earth sciences—A tutorial to the micrometer-scale mapping of molecular fossils via MALDI FT-ICR MS - Yannick Zander; Weimin Liu; Jannis Viola; Jenny Altun; Janina Groninga; Benjamin Nettersheim; Maria-Sofia Kapiri; Igor Obreht; Lars Wörmer (Analytica Chimica Acta, 2026)

Correction: Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2026)

Age-specific effects of density and weather on body condition and birth rates in a large herbivore, the Przewalski’s horse - Heiko G. Rödel; Benjamin Ibler; Katalin Ozogány; Viola Kerekes (Oecologia, 2023)
Reproduction in young females can show a particularly sensitive response to environmental challenges, although empirical support from individual-based long-term studies is scarce. Based on a 20-year data set from a free-roaming Przewalski’s horse population ( Equus ferus przewalskii ), we studied effects of large-herbivore density (horses + cattle) and weather conditions experienced during different life stages on females’ annual birth rates. Foaling probability was very low in 2-year-olds, reaching maximum values in 5 to 10-year-olds, followed by a decrease in older females indicating reproductive senescence. Mother’s previous reproductive investment affected her current reproduction; young and old mothers (as opposed to middle-aged ones), which had nursed a foal for at least 60 days during the previous year, reproduced with a lower probability. Foaling probability and body condition of young females were lower when large-herbivore density was high. Reproduction was also influenced by interactive weather effects during different life stages. Low late-summer precipitation during the females’ year of birth was associated with a pronounced decrease in foaling probability in response to harsh late-winter temperatures prior to the mating season. In turn, increased amounts of late-summer rain during this early age together with more late-summer rain during the females’ current pregnancy led to an increased reproductive probability in 2–3-year-olds. These results were corroborated by the ameliorating effects of late-summer rain on body condition in such females. In conclusion, our findings highlight the interactive importance of weather conditions experienced during early life, and of density and weather during current pregnancy on foaling probability, particularly in young females.

Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2023)
The relationships between flying Antarctic seabirds and their at-sea environments remain poorly understood, particularly outside of the breeding season. Improving our knowledge of how these marine predators use their habitat is a critical step towards conservation of these species. We tracked 27 adult Snow Petrels from two large breeding colonies in East Antarctica during the Austral winter (non-breeding period) – when they are primarily at sea away from their nesting sites. During this time, Snow Petrel habitat use was most associated with bathymetry (> 5000 m), low sea-surface height, relatively close distance to the southern boundary of the Antarctic Circumpolar Current, relatively close distance to the ice-edge, relatively high sea-ice concentration, and low sea-surface temperature. Individuals displayed various movement patterns: 20 birds occupied overlapping winter areas that ranged broadly (up to 2000 km) from their breeding sites. The remaining birds ventured far beyond their breeding sites – reaching a maximal distance from the colony of 5,268 km. One individual circumnavigated Antarctica. Daily activity patterns were related to day length, with peak activity occurring near dawn and dusk. Nocturnal activity increased from March until August/September. Key results reveal and depict Snow Petrel habitat maps for the non-breeding period in the East Antarctic region.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Visible light and near-infrared-responsive chromophores for drug delivery-on-demand applications - Chase S. Linsley; Viola Y. Quach; Gaurav Agrawal; Elyse Hartnett; Benjamin M. Wu (Drug Delivery and Translational Research, 2015)